Pruritus in pediatric patients with atopic dermatitis: a multidisciplinary approach - summary document from an Italian expert group - May El Hachem; Giuseppe Di Mauro; Roberta Rotunno; Simona Giancristoforo; Cristiana De Ranieri; Carla Maria Carlevaris; Maria Carmen Verga; Iride Dello Iacono (BMC, 2020)
Abstract Given the inadequate overall awareness of the main disease features and treatment modalities of pruritus in pediatric patients with atopic dermatitis, a multidisciplinary Italian expert group met with the major aim of increasing knowledge of the condition for improved diagnosis and better management among specialists involved in disease management. Herein, the overall features of the condition are reviewed, along with its etiopathogenesis and symptoms. Likewise, management options are summarized, emphasizing the need for a multidisciplinary approach, minimally composed of a management team that includes a pediatrician, dermatologist, psychologist, play assistant, and dedicated nurse. In addition to more traditional therapies such as emollients as highlighted by European guidelines, therapeutic patient education in a group or individually is highly encouraged as it helps patients and their parents to better understand the disease and provide practical guidance for dressing and bandaging. It can also aid in outlining coping strategies for itching and sleep disturbance. The utility of distraction techniques should also be stressed as such educational interventions involving the child and their parents can substantially improve the overall quality of life. All approaches should be tailored according to patient age and clinical features and requires individualized strategy to ensure good adherence by both children and their parents. Thus, a holistic approach embracing systemic, topical and psychological interventions is advocated in order to provide patients and their caregivers the best possible care.